Socioecological complexity in primate groups and its cognitive correlates - Shultz, S; Dunbar, RIM (Royal Society, 2022)
Characterising non-human primate social complexity and its cognitive bases has proven challenging. Using principal component analyses, we show that primate social, ecological and reproductive behaviours condense into two components: socioecological complexity (including most social and ecological variables) and reproductive cooperation (comprising mainly a suite of behaviours associated with pairbonded monogamy). We contextualise these results using a meta-analysis of 44 published analyses of primate brain evolution. These studies yield two main consistent results: cognition, sociality and cooperative behaviours are associated with absolute brain volume, neocortex size and neocortex ratio, whereas diet composition and life history are consistently associated with relative brain size. We use a path analysis to evaluate the causal relationships among these variables, demonstrating that social group size is predicted by the neocortex whereas ecological traits are predicted by the volume of brain structures other than the neocortex. That a range of social and technical behaviours covary, and are correlated with social group size and brain size, suggests that primate cognition has evolved along a continuum resulting in an increasingly flexible, domain-general capacity to solve a range of socioecological challenges culminating in a capacity for, and reliance on, innovation and social information use in the great apes and humans.